Analysis of authority management systems in automated document management systems - Durnyak, B. V.; Sikora, L. S.; Sabat, V. I.; Kuhot, V. O. (ТОВ «Друкарня Мадрид», 2023)
The article examines the features of the construction of the authorization management system for automated document management systems (ADMS), which is integrated into the structure of the hierarchy of organizations under the conditions of active attacks and threats to the information system. Based on the analysis of the terminal cycle of the technogenic hierarchy management process under the conditions of the risk of threats and attacks, the use of a conditional-modified authority management system is substantiated, which would take into account the specifics of the functioning of automated document management systems and would have the ability to respond to any negative changes or factors.
Keywords: management system; document